The Role of Teachers in The Formation of Character Value of Basic School Students Based in Pancasila in Digital 4.0 - Dian Candra Wati; Hana Zafirotul Khusna; Fildzah Kholishotul Azizah (Universitas Sebelas Maret, 2019)
This article aims to identify the importance of the teacher's role in shaping the values of Pancasila-based elementary school children in the digital age. The method used in the form of literature study by conducting a review of the literature, books, and reports relating to the case to be solved. Pancasila reflects the value of character which has an important role in character building. The role of the teacher in shaping the character of elementary school students, among others, is strengthening the foundation of faith, accustoming to good behavior, instilling values of unity, tolerance, tolerance, and being honest, moral, and responsible.